Research Cultures in the Modern University: Artificial Intelligence and Its Imperatives on Scientific Knowledge - Mututa, Addamms; Tomaselli, Keyan (Education as Change, 2025)
The university is traditionally mandated with training generations of scholars on knowledge production and maintaining the integrity of the knowledge production system. However, the advent of artificial intelligence (AI) tools and their wide adoption by researchers may challenge this mandate by altering research processes. This article discusses the changing research cultures arising from the use of AI tools in academic research and how these may occasion retrogressive research cultures. It uses exploratory methodology, engaging with literature and pertinent theories. The article’s main finding is that AI is widely used in various research stages. It also establishes the different viewpoints on AI usage, collating the wider African vision of scientific knowledge production. It concludes that AI affects cognitive-based learning and critical thinking, which may disrupt the succession of research cultures and divest the academe of its intellectual integrity. The article suggests an urgent review of AI use in universities to restore and maintain the integrity of knowledge production for the well-being of current and future societies.